Association of Medicaid expansion with birth outcomes: evidence from a natural experiment in Texas - Meryem Saygili; Esra Eren Bayindir (BMC, 2024)
Abstract Background Empirical evidence on the effects of Medicaid expansion is mixed and highly state-dependent. The objective of this study is to examine the association of Medicaid expansion with preterm birth and low birth weight, which are linked to a higher risk of infant mortality and chronic health conditions throughout life, providing evidence from a non-expansion state, overall and by race/ethnicity. Methods We used the newborn patient records obtained from Texas Public Use Data Files from 2010 to 2019 for hospitals in Texarkana, which is located on the border of Texas and Arkansas, with all of the hospitals serving pregnancy and childbirth patients on the Texas side of the border. We employed difference-in-differences models to estimate the effect of Medicaid expansion on birth outcomes (preterm birth and low birth weight) overall and by race/ethnicity. Newborns from Arkansas (expanded Medicaid in 2014) constituted the treatment group, while those from Texas (did not adopt the expansion) were the control group. We utilized a difference-in-differences event study framework to examine the gradual impact of the Medicaid expansion on birth outcomes. Results Medicaid expansion was associated with a 1.38-percentage-point decrease (95% confidence interval (CI), 0.09-2.67) in preterm birth overall. Event study results suggest that preterm births decreased gradually over time. Medicaid expansion was associated with a 2.04-percentage-point decrease (95% CI, 0.24-3.85) in preterm birth and a 1.75-percentage-point decrease (95% CI, 0.42-3.08) in low birth weight for White infants. However, Medicaid expansion was not associated with significant changes in birth outcomes for other race/ethnicity groups.  Conclusions Our findings suggest that Medicaid expansion in Texas can potentially improve birth outcomes. However, bridging racial disparities in birth outcomes might require further efforts such as promoting preconception and prenatal care, especially among the Black population.